Answer: t1 = 1 t2 = -2 t3 = -5 t4 = -8 common difference (d) = t2 – t1 = -2-1 = -3 = t3-t2= -5 – (-2) = -3 hence, the common difference is -3 Reply

To find the common difference Formula is :-D= a2-a1 -2-1 = -3 So -3 is the common difference between A1 and a2 Do the same prossece with A3 and a2 D= a3-a2 = -5-(-2)=-3 So the difference between all the A.p is -3 Reply

Answer:t1 = 1

t2 = -2

t3 = -5

t4 = -8

common difference (d) = t2 – t1 = -2-1 = -3

= t3-t2= -5 – (-2) = -3

hence, the common difference is -3

To find the common difference

Formula is :-

D= a2-a1

-2-1 = -3

So -3 is the common difference between A1 and a2

Do the same prossece with A3 and a2

D= a3-a2 = -5-(-2)=-3

So the difference between all the A.p is -3